THE COPING STRATEGIES EMPLOYED BY UNISA’S UNDERGRADUATE STUDENTS TO ADDRESS THE REALITIES EXPERIENCED WITH RESPECT TO THEIR LIVING CONDITIONS IN SUNNYSIDE, TSHWANE - Alpaslan, Assim Hashim (Social Work/Maatskaplike Werk, 2010)
A dearth of information about the realities related to the living conditions of Unisa’s undergraduate students in general emerged as a central research problem for an investigation into the realities and coping strategies relating to the living conditions of a sample of Unisa’s undergraduate students who reside in Sunnyside, Tshwane.